Research on Computer Network Data Security Storage Technology in the Era of Big Data - Zhang, L.; Gu, X.; Zhao, Q. (Revista internacional de métodos numéricos para cálculo y diseno en ingenieria, 2024)
In the burgeoning epoch of big data, the imperative for secure computer network data storage is confronted with formidable challenges, including the perils of data breaches and a paucity of robust security measures. An enhanced storage paradigm, predicated upon a refined Hash algorithm—termed H-AONT—is herein delineated. This methodology augments data storage security through the formulation of an apposite system model, the amalgamation of the merits inherent in conventional encryption algorithms, and the deployment of the H-AONT dual encryption algorithm in data processing. Empirical evidence substantiates that, vis-à-vis alternative approaches, the proposed method significantly bolsters data storage security, furnishes an elevated stratum of protection for computer network data repositories, ensures data storage reliability, and proffers a pertinent benchmark for the safeguarding of computer network data within the vast landscape of big data.